Resumo da actividade da Linguateca de 16 de Dezembro de 2006 a 31 de Dezembro de 2007 - Costa, Luís (2008)
Com a colaboração (por ordem alfabética) de Ana Frankenberg-Garcia, Cláudia Freitas, Diana Santos, Hugo Oliveira, Luís Costa, Luís Miguel Cabral, Paulo Rocha e Sérgio Matos